PENGARUH VARIASI SUSUNAN ARAH DAN FRAKSI VOLUME KOMPOSIT BERPENGUAT LIMBAH FILTER ROKOK SEBAGAI MATERIAL ALTERNATIF TERHADAP KEKUATAN TARIK DAN IMPAK - Dimas Aji Guntoro; Juanda Juanda; Muhammad Yunus (Politeknik Manufaktur Negeri Bangka Belitung, 2022)
Cigarette filter waste is something that we often find thrown carelessly in public places almost all over the world. Cigarette filters contain cellulose acetate, which is difficult to decompose naturally and takes a long time to decompose. In response to this, research is needed so that cigarette filter waste has use value and is useful as an effort to handle waste. One of them is by making cigarette butts as an alternative material made from composites. The purpose of this study was to determine the effect of variations in cigarette filter waste fibers on the tensile and impact strength of the polyester matrix. The fiber volume fraction includes 15% : 85%, 22.5% : 77.5%, 30% : 70% with horizontal, vertical and cross fiber directions. The material used is cigarette filter waste fiber. Standard ASTM D-638-1 is used as a reference for tensile tests and ISO 179-1 for impact tests. The results of this study showed that the maximum tensile strength of the fiber volume fraction was 15% with the cross-direction arrangement of 42 MPa and the maximum impact strength was found in the 30% fiber volume fraction and the cross-direction arrangement of 0.03068 J/mm2. Based on these results, the variation of the fiber volume fraction and the matrix affect the tensile and impact strength.